Kajian Potensi dan Efisiensi Energi Pembangkit Listrik Tenaga Surya (PLTS) di Wilayah Pekanbaru - Meriani meriani (Fakultas Teknik UMRI, 2017)
Indonesia is in the tropics has the potential of solar energy is very large about an average of 4.8 kWh / m2 / day or equivalent to 112,000 GWp, but which has been utilized only about 71.02 MWp of terintrkoneksi and off-grid therefore Solar energy to be an alternative The most widely developed and reliable. Solar power plants that have unlimited reserves and are environmentally friendly energy needs to be developed in accordance with the carrying capacity of Pekanbaru city which is included in the most potential irradiation zone that is five hours per day. This research studies the potential and efficiency of PLTS for the new weekend region in order to support the utilization of solar energy as an alternative power plant with the aim of obtaining the potential of electrical energy generated from the conversion of solar energy, obtaining the efficiency of solar energy conversion Pekanbaru region and Solar energy mapping in Pekanbaru region optimization Utilization of renewable energy potential in Pekanbaru City.Measurements are made on June 17, 2017 to 23 June 2017 and 06 July 2017 s / d 12 July 2017 at two locations namely Village Umban Sari district Rumbai and Simpang Baru Village District Tampan Kota. By using Monocrystalline type solar cell with Maximum Power 50 watt rate obtained efficiency result of 19.5% and energy peotensi equal to 85,462 Wh per day at first measurement point and 84,562 Wh per day at second point of measurement. For one house with 1200 VA power required approximately 15 Monocrystalline type solar cells with solar energy potential that can be generated by 1.275 Wh. Assuming 50% of the head of Pekanbaru city's population of approximately 250,000 households use solar energy, the potential of solar energy that can be utilized is 318 MWh. Suraya Energy can help approximately 25% of existing energy sources, namely PLTD, PLTA, and PLTU in the city of Pekanbaru.